Food, malls and the politics of consumption: South Africa's new middle class - (:unkn) unknown (My University, 2014)
Consumption has become a central focus in South African politics, one that hinges especially on evaluation of the behaviour of the new black middle class. Based on an ongoing ethnographic study of Durban, mainly among the lower middle or ‘professional’ class across a range of racial categories, the article addresses three aspects of this question: food provisioning and consumption across and within the various communities; interaction in shared social spaces that were previously segregated, especially shopping malls; and moral discourses in the media concerning this new class. The so-called 'black diamonds' are a South African urban type of the sort labelled by Benjamin as a phantasmagoria. South Africans are willing to experiment beyond the boundaries of their native communities and there is an emergent national middle-class culture, but there are marked regional differences and nothing yet that would amount to ‘creolisation’.
Keywords: African Research